Remarks on the Methodology of Comparative Legal Research in the Context of the History of Law in Poland - Gałędek, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
Is there anything outstanding about the history of law in Poland? Is it particularly conducive to comparative research? In my attempt to answer these questions, I focussed on presenting two distinct comparative law methods: historical legal comparison and comparative legal history. The paper is divided into two parts. The first part elaborates on the characteristics of the respective methods and on the challenges of comparative legal history in a temporally diachronic perspective and why they are not so pronounced in historical legal comparison. In this part, I tried to document the claim that the existence of a comparative platform of similarities is a condition to obtain more reliable and better-documented results of comparative research. In the second part, I focussed on three cases visualising the possibilities for comparative legal research on the history of law in Poland. Regarding the pre-partition times, I analysed the comparative possibilities related to an analysis of the impact of the Roman law on the Old Polish legal culture. The other two examples concerned the history of law in post-partition Poland. First, I explored the potential triggered by the adoption of foreign laws in Poland in terms of comparative research. I used French commercial law to exemplify the problem. Then, I undertook to show the dormant potential of the particular situation of Poland divided into different legal areas for the development of the country’s own codes of law.